Cell‐Free Human Papillomavirus‐DNA for Monitoring Treatment Response of Head and Neck Squamous Cell Carcinoma: Systematic Review and Meta‐Analysis. Issue 3 (8th July 2021) - Campo, Flaminia; Zocchi, Jacopo; Moretto, Silvia; Mazzola, Francesco; Petruzzi, Gerardo; Donà, Maria G.; Benevolo, Maria; Iocca, Oreste; De Virgilio, Armando; Pichi, Barbara; Manciocco, Valentina; Pellini, Raul
Abstract : Objectives/Hypothesis: The aim of this study was to assess the value of cell‐free human papillomavirus‐DNA (cfHPV‐DNA) as a diagnostic test for the post‐treatment surveillance of patients with HPV‐positive head and neck squamous cell carcinoma (HNSCC) through a systematic review and meta‐analysis. Study Design: Systematic review and meta‐analysis. Methods: A literature search was conducted in three databases (MEDLINE, Embase, and Scopus) in January 2021. The population included patients with HPV‐positive HNSCC. The intervention was the use of the repeated liquid biopsy with circulating HPV‐DNA detection during follow‐up. The outcome was to establish the value of cfHPV‐DNA as a diagnostic test for the post‐treatment surveillance of patients with HPV‐positive HNSCC. Results: Ten studies included in the meta‐analysis provided a total of 457 patients with HPV‐positive HNSCC. The meta‐analytic study estimated the diagnostic performance of cfHPV‐DNA as follows: pooled sensitivity and specificity of 0.65 (95% confidence interval [CI]: 0.40–0.84) and 0.99 (99% CI: 0.96–0.99), respectively; positive and negative likelihood ratios of 62.5 (99% CI: 22.9–170.2) and 0.05 (99% CI: 0.013–0.24), respectively; and pooled diagnostic odds ratio of 371.66 (99% CI: 60.4–2286.7). Conclusion: Currently, the follow‐up protocol for HNSCC patients includes routine clinical evaluation and radiological imaging. Biomarkers to monitor this disease are not established. Considering its high specificity, cfHPV‐DNA represents a potential confirmatory test in the case of positive positron emission tomography and computed tomography. In the near future, cfHPV‐DNA could be used as a biomarker for monitoring the treatment response during the clinical trials of de‐escalation therapy or immunotherapy. Larger sample sizes and the homologation of study protocols and methodology are needed to better establish its utility in the clinical practice. Laryngoscope, 132:560–568, 2022